VALERIANA OFFICINALIS: A REVIEW OF ITS TRADITIONAL USES, PHYTOCHEMISTRY AND PHARMACOLOGY - Nandhini, Sundaresan; Narayanan, Kasthuri Bai; Ilango, Kaliappan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Valeriana is a well-known Indian traditional medicinal herb with sleep remedy. It has been used over the years to treat nervine and sedative in hysteria, epilepsy, and sedative in nervous anxiety. It has also been used as an aromatic stimulant and reported some distinctive indications, as well as its use for rheumatism, low-grade fevers, and aphrodisiac. It has been known to grow well in regions of Europe, parts of Asia and North America. This systematic review focuses on the ethnopharmacological uses of Valeriana, including recent advances on the phytochemical and pharmacological study of Valeriana officinalis. In addition, future developments and scenarios in the study of the plant have been proposed. Various literature and electronic databases such as PubMed, ScienceDirect, Springer, and Wiley were searched and data obtained. Other online academic libraries such as Google Scholar and ethnopharmacological literature were searched systematically for more information on the plant. In this paper, we have reviewed various research conducted on V. officinalis especially in areas of its ethnopharmacological use, phytochemicals, and pharmacology. This plant has been used medicinally for a minimum of 2000 years. It is used in the treatment of brain disorder and also used for the treatment of varied nervous disorders, antispasmodic, anthelmintic, diuretic, diaphoretic, and emmenagogue, and hysteria. More research is needed in the area of pharmacokinetics and toxicology to give further information on the clinical use and control the quality of the plant.